2015
DOI: 10.1007/s12028-015-0167-0
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Neurological Life Support: Intracerebral Hemorrhage

Abstract: Intracerebral hemorrhage (ICH) is a subset of stroke due to bleeding within the parenchyma of the brain. It is potentially lethal, and survival depends on ensuring an adequate airway, reversal of coagulopathy, and proper diagnosis. ICH was chosen as an Emergency Neurological Life Support protocol because intervention within the first critical hour may improve outcome, and it is critical to have site-specific protocols to drive care quickly and efficiently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 73 publications
0
12
1
2
Order By: Relevance
“…According to the AHA/ASA guidelines [ 9 ] and the Emergency Neurological Life Support protocols [ 26 ], spontaneous intracranial hemorrhage is a medical emergency and should be managed accordingly. The initial management should focus on the following principles (Fig.…”
Section: Initial Evaluation and Clinical Stabilizationmentioning
confidence: 99%
“…According to the AHA/ASA guidelines [ 9 ] and the Emergency Neurological Life Support protocols [ 26 ], spontaneous intracranial hemorrhage is a medical emergency and should be managed accordingly. The initial management should focus on the following principles (Fig.…”
Section: Initial Evaluation and Clinical Stabilizationmentioning
confidence: 99%
“…The Emergency Neurological Life Support (ENLS) Guidelines recommend that the following be completed within the first hour of presentation: complete blood count with platelet and prothrombin time (PT), partial thromboplastin time, and international normalization ratio (INR); brain imaging to determine size and location of hematoma; and Glasgow Coma Score (GCS) and ICH scores. 20 The utility of the National Institute of Health Stroke Scale (NIHSS) score may be diminished with depression in the level of consciousness that can accompany ICH. 4 Though it is not clear which severity score is optimal, the ICH and NIHSS scores are the most commonly used and provide a common language by which specialists can communicate.…”
Section: Emergency Department Managementmentioning
confidence: 99%
“…4 Airway and ventilation management, initiation of blood pressure control, and coagulopathy reversal, if needed, should all be initiated within the first hour. 20 Patients with ICH frequently require management in a critical care setting where close monitoring and quick intervention can be instituted. A 4-year single center retrospective study showed a fourfold increase in poor functional outcome and discharge NIHSS in patients who stayed longer than 5 hours in the ED.…”
Section: Emergency Department Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…83 However, in clinical practice, concern for thrombotic complications of activated PCC may lead some to prefer rFVIIa or nonactivated PCC for reversing dabigatran until more prospective data are available. 84 Activated charcoal may be considered if ingestion of dabigatran was within 2 hours of hospital admission. Furthermore, intermittent hemodialysis effectively neutralizes 66% of the anticoagulant effect of dabigatran 80,85 ; however, its utility in ICH may be limited by the induced fluid shifts and rebound anticoagulant effect.…”
Section: Direct Thrombin Inhibitorsmentioning
confidence: 99%